A Dynamic Selection Algorithm on Optimal Auto-Response for Network Survivability - Jinhui Zhao; Yujia Sun; Liangxun Shuo (Institute of Advanced Engineering and Science, 2014)
In the selection process of survival strategies, it is a challenging work to automatically choose the optimal measure for the survival event. A dynamic selection algorithm is proposed, based on feedback control. According to the feature of survival strategy, the strategy model is presented, which includes fuor specific attribute. The dynamic update process of attribute vector is described in detail. Combining the weight of preference and attributes of strategy, the TOPSIS evaluation is employed to select optimal measure. Experiments and analysis show that optimal measure selected by proposed algorithm is appropriate and wishful, which enriches the research content in this field.